Religio-scientific integration of knowledge: A study of islam's prophetic traditions related to the medical sciences - Mohd Zohdi Mohd Amin; Tazul Islam; Mohd Yusuf Ismail; A. Irwan Santeri Doll Kawaid; Adnan Mohamed Yusoff; Mesbahul Hoque; Mohammed Akhiruddin Ibrahim; Mohd. Fauzi Mohd. Amin; Shumsudin Yabi; Samer Najeh Abdullah Samarh; Kauthar Abd Kadir; Abas, Siti (American Scientific Publishers, 2024)
Indexed by Scopus/ERA